2020
DOI: 10.3389/fphys.2020.01037
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immune Cells on the Skeletal Muscle Microenvironment During Cancer Cachexia

Abstract: Progressive weight loss combined with skeletal muscle atrophy, termed cachexia, is a common comorbidity associated with cancer that results in adverse consequences for the patient related to decreased chemotherapy responsiveness and increased mortality. Cachexia’s complexity has provided a barrier for developing successful therapies to prevent or treat the condition, since a large number of systemic disruptions that can regulate muscle mass are often present. Furthermore, considerable effort has focused on inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 255 publications
(383 reference statements)
0
36
0
Order By: Relevance
“…Several preclinical studies have suggested the possibility of an interplay between cell metabolism and susceptibility to immunotherapy. The contribution of neutrophils, monocytes, and T-cell types to myofiber composition and microenvironment has been documented, as well as to the processes of skeletal muscle damage, repair, remodeling, inflammation and fibrosis [ 62 ]. Along this line, a number of clinical studies have reported the association between BMI and the effectiveness of ICIs in patients with advanced melanoma [ 63 ], lung cancers [ 64 ], or triple negative breast tumors [ 65 ].…”
Section: Nutritional Care During Immunotherapy: Does the Boundless Prairie Have A Fence?mentioning
confidence: 99%
“…Several preclinical studies have suggested the possibility of an interplay between cell metabolism and susceptibility to immunotherapy. The contribution of neutrophils, monocytes, and T-cell types to myofiber composition and microenvironment has been documented, as well as to the processes of skeletal muscle damage, repair, remodeling, inflammation and fibrosis [ 62 ]. Along this line, a number of clinical studies have reported the association between BMI and the effectiveness of ICIs in patients with advanced melanoma [ 63 ], lung cancers [ 64 ], or triple negative breast tumors [ 65 ].…”
Section: Nutritional Care During Immunotherapy: Does the Boundless Prairie Have A Fence?mentioning
confidence: 99%
“…1 . In addition to those discussed, further evidences strongly indicates a potential role of altered immune function in CC, these alterations have been recently described in a review by VanderVeen et al 113 and thus will not be described here. However, they may be critical to understanding the full spectra of this condition and appropriate therapeutic strategies.…”
Section: Alterations To Non-skeletal Muscle Tissues During Development and Progression Of CCmentioning
confidence: 88%
“…Three possible mechanisms underlying muscle loss during chemotherapy have been considered: (1) decreased food intake due to gastrointestinal adverse effects, (2) reduced physical activity secondary to general fatigue, and (3) direct effect of chemotherapy on muscles [26]. Furthermore, as another mechanism, the indirect effect of chemotherapy on muscle alteration via immune cells was suggested [30]. Wang et al showed that T cells could attenuate muscle mass loss during cancer progression [31].…”
Section: Discussionmentioning
confidence: 99%